Legal Significance of Digitalization of Environmental Information in Ensuring Environmental Safety - BEKEZHANOV, Dauren; RZABAY, Aktoty; NESIPBAEV, Olzhas; KOPBASSAROVA, Feruza; HALIBIYATI, Halibati (Journal of Environmental Management and Tourism; Vol 13 No 3 (2022): JEMT, Volume XIII, Issue 3(59), Summer 2022DO - 10.14505/jemt.v13.3(59).06, 2022)
The article is devoted to the study of legal problems, studies of the importance of digitalization of environmental information in ensuring environmental safety have been conducted. In addition, studies have been conducted on the possibility of digitalization of information in the field of environmental protection and the use of natural resources to address issues of the effectiveness of environmental policy implementation, compliance with environmental standards and requirements, participation in the adoption of environmentally significant decisions of measures to coordinate the activities of state and other bodies in ensuring the environmental safety of the country. The legal experience of foreign countries has been carefully studied in this area. Specific recommendations are given to the basics of state regulation of digitalization of collection, analysis and accumulation of environmental information in ensuring environmental safety, topical issues of both state bodies and in the field of environmental, legal and information digitalization. The study of the problems of digitalization of environmental information was considered as a set of legal, economic, organizational, technical measures aimed at ensuring environmental safety, protecting the rights and interests of the state, individuals, and legal entities in the field of environmental protection and the use of natural resources, ensuring cybersecurity in the field of environmental information.